System grzewczy zamku w Narzymiu. Wstępna próba rekonstrukcji - Marciniak-Kajzer, Anna (Acta Universitatis Lodziensis. Folia Archaeologica, 2010)
Excavations in Narzym near Działdowo began in 2003. In the Middle Ages this area belonged to the Teutonic knights state. Within three research seasons an area of 454.55 m2 was excavated (fig. 1). Remains of a stronghold with a stone cylindrical tower from the 2nd half of the 14th century and of a castle built in the turn of the 15th and 16th centuries (fig. 3) were discovered. For the whole time this seat belonged to private owners what is an absolute exception in the Teutonic knights state. Earlier object was heated probably by a stove of pot tiles (fig. 7). Whereas, in the castle a stove (stoves?) of bowl tiles with square hole (fig. 4a and 4b) functioned, and heating of hypocaustum type, what is testified by and of a fragment of heating hole framing (fig. 6). Hypocaustic heating was relatively popular in the area of the Teutonic knights state, however the functioning of central heating system in magnate’s seat was stated for the first time.